Socioeconomic status predicts second cardiovascular event in 29, 226 survivors of a first myocardial infarction. (June 2018) - Ohm, Joel; Skoglund, Per H; Discacciati, Andrea; Sundström, Johan; Hambraeus, Kristina; Jernberg, Tomas; Svensson, Per
Background: Risk assessment post-myocardial infarction needs improvement, and risk factors derived from general populations apply differently in secondary prevention. The prediction of subsequent cardiovascular events post-myocardial infarction by socioeconomic status has previously been poorly studied. Design: Swedish nationwide cohort study. Methods: A total of 29, 226 men and women (27%), 40–76 years of age, registered at the standardised one year revisit after a first myocardial infarction in the secondary prevention quality registry of SWEDEHEART 2006–2014. Personal-level data on socioeconomic status measured by disposable income and educational level, marital status, and the primary endpoint, first recurrent event of atherosclerotic cardiovascular disease, defined as non-fatal myocardial infarction or coronary heart disease death or fatal or non-fatal stroke were obtained from linked national registries. Results: During the mean 4.1-year follow-up, 2284 (7.8%) first recurrent manifestations of atherosclerotic cardiovascular disease occurred. Both socioeconomic status indicators and marital status were associated with the primary endpoint in multivariable Cox regression models. In a comprehensively adjusted model, including secondary preventive treatment, the hazard ratio for the highest versus lowest quintile of disposable income was 0.73 (95% confidence interval 0.62–0.83). The association between disposable income and first recurrent manifestation of atherosclerotic cardiovascular disease was stronger in men as was the risk associated with being unmarried (tests for interaction P < 0.05). Conclusions: Among one year survivors of a first myocardial infarction, first recurrent manifestation of atherosclerotic cardiovascular disease was predicted by disposable income, level of education and marital status. The association between disposable income and first recurrent manifestation of atherosclerotic cardiovascular disease was independent of secondary preventive treatment but further study on causal pathways is needed.